Determinant of firm financial performance: Case of Indonesian conventional banks - Silvi Aditya Wilujeng; Fadilla Cahyaningtyas (Akuntansi dan Teknologi Informasi, 2023)
The objective of this study is to assess the influence of good corporate governance, intellectual capital, credit risk, and sales growth on the financial performance of conventional banking firms that are listed on the Indonesia Stock Exchange throughout the period of 2018-2021. The sample approach employed in this study is purposive sampling. The sample size consists of 21 firms. Various data analysis approaches employ normality testing, double regression tests, hypothesis tests, and determination coefficient tests. The findings indicate that there is no significant relationship between corporate governance performance, intellectual capital, credit risk, sales growth, and financial performance. The results of this study provide practical implications, especially for investors and management of banking companies to consider various factors in improving the company's financial performance.